In Silico and In Vitro Studies on an Asymmetrical Porphyrin Derivative with Therapeutic Potential in Skin Disorders - Andreea Mihaela Burloiu; Dragos Paul Mihai; Gina Manda; Dumitru Lupuliasa; Ionela Victoria Neagoe; Radu Petre Socoteanu; Mihaela Surcel; Laurentiu-Iliuta Anghelache; Laura Olariu; Cerasela Elena Gîrd; Rica Boscencu (MDPI AG, 2024)
For developing novel photosensitizers with therapeutic potential in non-malignant and malignant cutaneous disorders, the unsymmetrical porphyrin, 5-(2-hydroxy-3-methoxyphenyl)-10, 15, 20-tris-(4-carboxymethylphenyl) porphyrin, was evaluated in silico and in vitro. The cellular uptake of the investigated porphyrin and its ability to perform photodynamic therapy were investigated in terms of the viability, proliferation, and necrosis of human HaCaT keratinocytes and human Hs27 skin fibroblasts, in correlation with the predictions regarding diffusion through cell membranes, ADMET profile (absorption, distribution, metabolism, elimination, toxicity), and potential pharmacological mechanism. Molecular docking and 250 ns molecular dynamics simulations revealed that P5.2 has the potential to form a relatively stable complex with the carbonic anhydrase IX catalytic site, the lowest predicted free energy of binding (MM/PBSA) being −39.097 kcal/mol. The results of the in vitro study showed that P5.2 is incorporated within 24 h in the investigated cells, especially in HaCaT keratinocytes, indicating its photosensitizing ability. Nevertheless, P5.2 does not exert significant cytotoxicity in "dark" conditions. In turn, PDT induced a decrease in the number of metabolically active HaCaT keratinocytes within 24 h, accompanied by a 4-fold increase in lactate dehydrogenase release, indicating its ability to perform PDT in human skin cells. The experimental results suggest that the asymmetrical porphyrin is a promising candidate theranostics agent for skin disorders.